MODEL PERSAINGAN PASAR MONOPOLISTIK DALAM PENENTUAN HARGA OBAT PADA MASA PANDEMI COVID-19 - Sofiah, Sofiah; Rizkiya, Tri Wahyu; Annizar, Anas Ma'ruf (Universitas Muhammadiyah Surabaya, 2022)
Competition between pharmacies is increasing, especially during the pandemic, so they have to compete with each other for marketing strategies. The purpose of this study is to describe the determination of drug prices and income levels during the pandemic. The type of research used is descriptive with a qualitative approach. The results showed that the determination of drug prices at Kraksaan pharmacies in three pharmacies in the city had different standards. In determining drug prices, pharmacies use the HET standard or commonly known as the highest retail price. However, there are also pharmacies that have their own standard price with a percentage of the purchase price with an agreed number and have an agreed price at the beginning of the VAT price. At the kraksaan city pharmacy, there are a number of drugs that are above HET and below HET with additional margins that have been determined at each pharmacy. In addition, income at pharmacies in the city of Kraksaan has increased more during the COVID-19 pandemic. This is due to a number of factors, one of which is the condition of society during the pandemic. When people experience complaints, they will buy drugs at pharmacies, therefore income at pharmacies has increased during the pandemic